Antimicrobial, anti-biofouling, antioxidant, and biocompatible fabrics with high durability via green growth of trimetallic nanoparticles - Sahin, Gamze Demirel; Sahin, Furkan; Barlas, Firat Baris; Onses, Mustafa Serdar; Acar, Serap (ELSEVIER, 2024)
There is a high demand for green and sustainable multifunctional fabrics, which find application in a variety of real-life contexts. This study addresses the development of antimicrobial, antioxidant, anti-biofouling and biocompatible fabrics through a one-step, versatile and cost-effective in-situ green growth strategy. Monometallic, bimetallic and trimetallic nanoparticles comprising silver (Ag), copper (Cu) and zinc (Zn) were grown in-situ on fabric surfaces using Sideritis scardica extract. The average size of nanoparticles was 99 +/- 25 nm, 131 +/- 29 nm, 68 +/- 18 nm for Ag, Cu and Zn. The metallic nanoparticles grown on the fabric surface imparted a range of colors to the fabrics, including yellow, brownish and greenish hues. Nanoparticle-decorated fabrics have antimicrobial, antioxidant, anti-biofouling, biocompatibility, and high durability properties. The decoration of fabrics with metallic nanoparticles mediated antimicrobial properties against bacteria (E. coli and S. aureus) and fungi (C. albicans), achieving a reduction of over 99.99 % (Logarithmic reduction>4). Bimetallic and trimetallic Ag and Cu nanoparticles exhibited enhanced antifungal activity in comparison to their monometallic counterparts. The cytotoxic effects of Cu were effectively eliminated through the fabrication of bimetallic nanostructures containing Zn. Notably, the biocompatibility of monometallic and bimetallic combinations involving Ag and Zn exceeded 95 %. The water contact angles of the decorated fabrics ranged from 145 degrees to 153 degrees. The superhydrophobic character of the fabrics prevented pathogen adhesion and inhibited biofilm formation. Moreover, all nanoparticle-decorated fabrics demonstrated antioxidant properties, with radical-scavenging activity ranging from 46 % to 91 %. The fabrics retained their antimicrobial properties against mechanical abrasion, heating and repeated cycles of washing and bending.
Keywords: Antimicrobial; Anti-biofouling; Antioxidant; Metallic nanoparticles; Green fabrication; Durability; ZINC-OXIDE NANOPARTICLES; SILVER NANOPARTICLES; OXIDATIVE STRESS; ANTIBACTERIAL; COPPER; INHIBITION; METAL; Materials Science